2020
DOI: 10.21203/rs.3.rs-45983/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical features of patients with hepatic portal venous gas

Abstract: Background: Hepatic portal venous gas (HPVG) is a rare clinical condition that is caused by a variety of underlying diseases. However, the factors that would permit accurate identification of bowel ischemia, requiring surgery, in patients with HPVG have not been fully investigated.Methods: Thirty patients that had been diagnosed with HPVG using computed tomography between 2010 and 2019 were allocated to two groups on the basis of clinical and intraoperative findings: those with (Group 1; n = 12 [40%]) and with… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In a retrospective analysis of 30 patients with imaging evidence of PVG, intestinal ischemia was the cause in 40% of the patients and 60% of PVG were due to other causes [17]. These included enteritis (33%), bowel distension (2%), pneumothorax (3.3%) or unknown causes (3.3%) [17]. A more recent analysis by Daneshment et al [8] of 10 years of data found 164 patients with PVG [8].…”
Section: Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…In a retrospective analysis of 30 patients with imaging evidence of PVG, intestinal ischemia was the cause in 40% of the patients and 60% of PVG were due to other causes [17]. These included enteritis (33%), bowel distension (2%), pneumothorax (3.3%) or unknown causes (3.3%) [17]. A more recent analysis by Daneshment et al [8] of 10 years of data found 164 patients with PVG [8].…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In addition to intestinal ischemia and intestinal necrosis Alataby et al [13] described PVG after recurrent vomiting and Biphasic Positive Airway Pressure (BIPAB)-ventilation. In a retrospective analysis of 30 patients with imaging evidence of PVG, intestinal ischemia was the cause in 40% of the patients and 60% of PVG were due to other causes [17]. These included enteritis (33%), bowel distension (2%), pneumothorax (3.3%) or unknown causes (3.3%) [17].…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation